2011
DOI: 10.1051/0004-6361/201015465
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of AMAZE and LSD galaxies from gas kinematics and the Tully-Fisher relation atz  ~  3

Abstract: We present a SINFONI integral-field kinematical study of 33 galaxies at z ∼ 3 from the AMAZE and LSD projects, which are aimed at studying metallicity and dynamics of high-redshift galaxies. The number of galaxies analyzed in this paper constitutes a significant improvement over existing data in the literature, and this is the first time that a dynamical analysis is obtained for a relatively large sample of galaxies at z ∼ 3. Eleven galaxies show ordered rotational motions (∼30% of the sample). In these cases … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
266
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(292 citation statements)
references
References 56 publications
24
266
2
Order By: Relevance
“…In the table, companions have the suffix "s". The model rotation curve only reproduces the velocity field and is not based on a gravitational potential model (as for instance in Förster Schreiber et al 2006;Cresci et al 2009;Gnerucci et al 2011) since the shape of the gravitational potential is unknown and can probably not be described by a stellar component only. Note that a gaseous thin disk in rotation is not incompatible with a spheroidal stellar distribution such as was observed in local ellipticals (e.g.…”
Section: Kinematics Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the table, companions have the suffix "s". The model rotation curve only reproduces the velocity field and is not based on a gravitational potential model (as for instance in Förster Schreiber et al 2006;Cresci et al 2009;Gnerucci et al 2011) since the shape of the gravitational potential is unknown and can probably not be described by a stellar component only. Note that a gaseous thin disk in rotation is not incompatible with a spheroidal stellar distribution such as was observed in local ellipticals (e.g.…”
Section: Kinematics Modelingmentioning
confidence: 99%
“…From the IMAGES sample at 0.4 < z < 0.75 (Yang et al 2008;Neichel et al 2008;Puech et al 2008;Rodrigues et al 2008), it has been shown that regular rotating disks are quite similar to local rotators and that merging is playing a significant role in galaxy mass assembly. At higher redshift, the SINS sample at z ∼ 2.2 Shapiro et al 2008;Förster Schreiber et al 2009;Shapiro et al 2009;Cresci et al 2009), the LSD/AMAZE sample at z ∼ 3.3 (Gnerucci et al 2011) and the sample built by Law et al (2009) at 2 < z < 3 are all containing many galaxies with high gaseous turbulence. Based on numerical simulation results of unstable gas-rich disks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have taken advantage of this technique to study the gas dynamics of distant galaxies, from z ∼ 0.6 (Flores et al 2006) up to z 2 (Förster Schreiber et al 2009;Law et al 2009;Epinat et al 2009;Gnerucci et al 2011). Recently, the Mass Assembly Survey with SINFONI in VVDS (MASSIV; Contini et al 2012) has collected data of z ∼ 1−2 galaxies observed with the integral-field spectrograph SINFONI at the VLT (Eisenhauer et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bell & de Jong 2001;Pizagno et al 2007;Meyer et al 2008;Gurovich et al 2010) and intermediate and high redshifts (e.g. Conselice et al 2005;Flores et al 2006;Atkinson et al 2007;Kassin et al 2007;Puech et al 2008;Cresci et al 2009;Gnerucci et al 2011) has been the subject of numerous works. Although many authors suggest the existence of evolution, observational results have not converged yet, and it is also unclear if the evolution is present in the zero point, the slope, or in both (Vogt et al 1996(Vogt et al , 1997Nakamura et al 2006).…”
Section: Introductionmentioning
confidence: 99%